Discourse Analysis of Male Sterilization in Rwanda’s Family Planning Policy Practice - Mutijima Pacifique; Herizal Herizal (Department of Government Studies, Universitas Syiah Kuala, 2022)
This article intends to analyze the discourse of male sterilization (vasectomy) in Rwanda’s family planning practice. It seeks to understand the public opinion towards the vasectomy as a birth control tool in Rwanda. The Family Planning Vision 2020 (FP2020) forum started in 2012 and more than 150 political leaders met at the London Summit on Family Planning agreed to give 120 million women in the world’s poorest countries access to contraceptives by the year 2020. Rwanda has made great achievement toward these goals and the current trend in Family Planning use is encouraging. However, despite the explanations provided by the Government of Rwanda on the necessary need of family planning, many people including the religious leaders have different understanding on the family planning especially the male sterilization. By examining the discourse on family planning practices, this article demonstrates the different perception about vasectomy operation in Rwanda. The article is based on documents analysis and uses the methodology of political discourse theory.